Telenursing in Health Services in the Era of the COVID-19 Pandemic: Literature Review - I Made Rai Mahardika; Luh Gde Nita Sri Wahyuningsih; Putu Ayu Lestarini (Babali Health, 2022)
Introduction: The development of telenursing is very rapid in various countries. The practice of telenursing supports nurses in providing care to patients without requiring nurses to meet directly with patients so as to reduce the spread of COVID-19 from nurses to patients, or vice versa. Telenursing is an alternative in providing health and long-distance services during the COVID-19 pandemic era. This literature review aims to determine the benefits of telenursing in health services in the COVID-19 pandemic era. Methods: The method used is a literature study analyzed from several journals. related to the topic taken. Journals were searched through ProQuest, EBSCO and google scholar with keywords telenursing, COVID-19 and health services. Results: The results of 11 articles show the benefits of telenursing in health services, including preventing the transmission of COVID-19 infection, media and health counseling, analysis costs and sustainable health services. Conclusion: Telenursing is one of the answers in overcoming the changes that occur to meet the needs of health access in the community. The application of telenursing during the COVID-19 pandemic provides various benefits for both patients and health workers. Telenursing has positive implications in preventing the transmission of COVID-19, as a medium for counseling and health promotion, minimizing medical costs and as a continuity of care.